Trauma Functioning and Well-Being in Children Who Receive Mental Health Aid after Natural Disaster or War - Emily A. Simonds; Katrina Arlene P. Gobenciong; Jonathan E. Wilson; Michael R. Jiroutek; Nicole R. Nugent; Miranda A. L. van Tilburg (MDPI AG, 2022)
Background: There is worldwide consensus that providing secondary prevention to promote resilience and prevent mental health concerns after a disaster is important. However, data supporting this kind of intervention is largely lacking. The current study evaluates the effectiveness of OperationSAFE, an early intervention for children after community-wide trauma. Methods: Secondary data analyses of data collected during 158 OperationSAFE camps (a five day camp with a curriculum focused on coping with stressors) in five countries and ten disasters between 2015 and 2020 were performed. Data on child trauma-related functioning/well-being were collected by an OperationSAFE in-house developed symptom checklist and completed by counselors about children on the first and last day of the 5-day camp. Results: A total of 16,768 children participated in the camps (mean age 9.4 ± 2.36; 50% male). Trauma-related functioning/well-being improved from day 1 to day 5 (b = 8.44 ± 0.04; p < 0.0001). Older children improved more (b = 0.22 ± 0.01; p < 0.0001). Children in man-made ongoing trauma (war/refugees) situations responded stronger than those after natural disasters (b = 2.24 ± 0.05; p < 0.0001). Negligible effects for gender and the number of days between a traumatic event and the start of camp were found. Conclusions: This is the first study to show in a large and diverse sample that secondary prevention to promote resilience and prevent mental health concerns after a disaster for children is associated with improvements in trauma-related functioning/well-being. Delaying delivery of the intervention did not affect outcomes. Given the uncontrolled nature of the study and lack of long-term outcomes, more studies are needed to corroborate the current findings.